The Relationship between Science Teachers’ Self-Efficacy Perceptions towards 21st Century Skills and their STEM Attitudes - Ugur Sari; Esra Balkas-Yasar (Journal of Education in Science, Environment and Health)
Students are expected to have 21st century skills and be STEM literate for successful future careers. Teachers who will include teaching practices to develop these skills should have these competencies. Therefore, it is important how teachers perceive 21st century competencies and STEM education or what kind of tendencies they have in this context. This study aims to examine science teachers’ self-efficacy perceptions towards 21st century skills and their STEM attitudes and to reveal the relationship between them. Fifty teachers working in a city in Turkey participated in the study in which the concurrent mixed methods research design was used. Scales of self-efficacy perceptions towards 21st century skills and STEM attitudes were used as data collection tools. Independent sample t-test, Mann Whitney U test (MWU), Kruskal Wallis-H test (KWH) and Spearman Correlation analysis were used in the analysis of the data. In the study, a significant and positive relationship was determined between teachers’ self-efficacy perceptions and their STEM attitudes. It was determined that teachers with self-efficacy perception had positive STEM attitudes. Qualitative data consisting of teachers’ opinions supports these findings. It was observed that while teachers’ gender and professional seniority did not make a difference in self-efficacy perceptions, STEM attitudes differed in favour of women according to gender, and there was no difference according to professional seniority.